Study on nonlinear asymmetric thermomechanical stability of microsize FGM curved beams based on nonlocal couple stress curvature sensitive model - Saeid Sahmani; Kamila Kotrasova; Muhammad Atif Shahzad; Veronika Valaskova; Mona Zareichian; Babak Safaei (Results in Engineering)
In the ongoing research examination, a meshfree-based numerical curvature sensitive framework is advanced to analyze the nonlinear asymmetric thermomechanical stability characteristics of microsize curved beams composed of functionally graded materials (FGMs) and subjected to an arbitrary-located concentrated load, uniform temperature rise as well as diverse end supports. As a means to apprehend size dependencies, the nonlocal couple stress theory (NCST) continuum elasticity theory is executed contingent the fifth-order shear flexible curved beam formulations incorporating the thickness stretch. Therefore, as a pioneer exploration, the size-dependent curvature sensitive model of concentrated loaded microsize curved beam is mathematically formulated. To originate the numerical curvature sensitive model, the radial point interpolation meshfree technique is utilized embracing the variation of the nodal points density based upon the background decomposition method (BDM). It is realized that the temperature rise causes to elevate the concentrated loads attributed to the upper limit points, while it leads to decline the concentrated loads associated with the lower limit points. Also, by combination of the softening consequence related to the nonlocal stress tensor with high temperature rise, the number of detected limit points allied to the small curvature sensitivity parameter increases from two points to four points.